The Triarchic Psychopathy Measure (TriPM): alternative to the PCL-R? - Evans, Lydia; Tully, Ruth (Elsevier Masson, 2016)
Psychopathic personality disorder is the subject of many research papers and in particular in the context of forensic settings, where its link to risk of future violence has been established. This topic is well examined but there is still considerable debate about the nature of the construct and how psychopathy is measured. Contemporary models such as the triarchic theory (Patrick, Fowles & Krueger, 2009) have been put forward yet the research into psychopathy tends to rely on one assessment tool, the Psychopathy Checklist-Revised (PCL-R; Hare, 2003) that is argued not to capture elements of psychopathy such as boldness. The Triarchic Psychopathy Measure (TriPM; Patrick, 2010) is a measure that is based on the triarchic theory, and it places an equal focus on boldness when measuring psychopathy. It is however a self-report instrument, and this approach has many limitations. This paper aims to review the scientific support for the TriPM and to discuss its potential application to clinical practice. It concludes that the TriPM may not yet be a contender for the PCL-R throne as the sole tool of choice for psychopathy measurement, but the research into the application of the TriPM is expanding our understanding of psychopathy as a construct.